An Analysis of the Predictive Value of Business Cycle Indicators on South Afica’s Stock Market Performance: Array - Chipeta, Chama; Dickason, Zandri (Acta Universitatis Danubius. Œconomica, 2021)
The financial market’s capital market stability and development are core drivers of progressive, sound and well-functioning economic operations relied upon in both the macro-and micro-economic spheres. The stock market, a key component of the capital market, generates substantial opportunities for businesses, traders, and investors. The stock market remains a daunting securities platform amid heightening uncertainty and market disruptions. In order to broaden the mechanisms for coherent understanding and interpretation of stock market performance, this study seeks to bridge the gap between the financial and the real economy through the utilization of business cycle indicator’s (BCI) component series of the composite indicators, as potential leading signals of South Africa’s stock market performance. In scrutinizing the concordance and usefulness of BCIs as key signals for stock market analysis, the study employed a cross-correlations test, Granger causality model, variance decomposition and charting techniques. Monthly observations from June 2003 to November 2017 were used. Findings revealed that most BCIs showcase significant leading, lagging and coinciding properties in explaining stock market behaviour. A myriad of indicators identified as leading stock market signals, where combined to form a single leading index, and successfully led the durational gap in South Africa’s stock prices at consecutive periods. Based on the findings, inferences were made that BCIs are noteworthy signals for market analysis and interpretation.